Weizmannia coagulans: an ideal probiotic for gut health - Shiqi Zhang; Pinglan Li; Suwon Lee; Yu Wang; Chunming Tan; Nan Shang (Food Science and Human Wellness)
Weizmannia coagulans (formerly Bacillus coagulans) is a spore-forming and lactic acid-producing bacterium. It has recently attracted much attention from researchers and food manufacturers due to its probiotic functions and stability in processing and storage. W. coagulans is capable of improving gut health through the regulation of gut microbiota, modulation of immunity, and improving digestibility and metabolism. Spores, germinated cells and metabolites of W. coagulans modulate the gut micro-environment and further affect other organs. W. coagulans is an environment-friendly probiotic since it can contribute to the host by reconstructing the balance of gut microbiota and only temporarily resides in the intestine after administration. W. coagulans has been generally recognized as safe (GRAS) by the US Food and Drug Administration (FDA), thus it is an ideal probiotic for improving gut health. The merit of its stability in processing and storage provides W. coagulans spores many possibilities for its use in various types of functional foods. This review presents an overview of the characteristics of W. coagulans that make it an ideal probiotic candidate and highlights the proposed health benefits with scientific evidence conferred by the administration of W. coagulans.